Level of anxiety and depression and problems related to alcohol use in employees of a public university (Research, Society and Development, 2021)
Objective: The objective of the study was to estimate the prevalence of anxiety and depression and to identify problems related to alcohol use; in addition to verifying the existence of an association between these factors and sociodemographic and labor variables of teachers and technical-administrative employees of the Faculties of Dentistry (FO) and Veterinary Medicine (FMV) of Araçatuba - Universidade Estadual Paulista. Methods: For this, the database was analyzed from January 2013 to October 2019, referring to the questionnaires applied annually during the periodic examination of employees and teachers of the institutions. They consist of the Hospital Anxiety and Depression Scale (HADS), for the assessment of anxiety and depression; in the Alcohol Identification Problems Test (AUDIT), for the identification of harmful use and alcohol dependence and in the Self-Report Questionnaire (SRQ), for tracking non-psychotic disorders, called Common Mental Disorders (CMD) . Results: In the analyzed period, 2971 periodic examinations were performed, with 569 (19.2%) showing some alteration. Of these, 429 (75.4%) had changes in the HADS anxiety questionnaire, 254 (44.6%) in HADS depression, 81 (14.2%) in AUDIT and 312 (54.8%) in SRQ. The mean age was 52.23 years (sd = 8.62). Most of the people who had changes in the psychic exam were female (57.3%), technical-administrative servers (64.3%) and the FO (67.3%). There was an association between CMD and problems related to alcohol use with sociodemographic variables. It is concluded that the prevalence of CMD and problems related to alcohol use in the studied population is relatively low. Despite this, there is an association between these factors and sociodemographic and labor variables.